Clinical study and outcome of alcoholic and nonalcoholic acute pancreatitis presenting to a tertiary care center - T., Kemparaj; G. S., Mridul (International Surgery Journal, 2018)
Background: Acute pancreatitis is a common condition involving the pancreas. The estimated incidence is about 3% of cases presenting with pain abdomen. The study is undertaken to study the various etiological factors and clinical factors of alcoholic and nonalcoholic acute pancreatitis and to assess the prognosis, outcome, management of an alcoholic and nonalcoholic acute pancreatitis. Methods: A total of 60 cases from BMCRI hospital attached selected during the study period from November 2015 to June 2017. Results: In the present study total 60 patients with acute pancreatitis were enrolled, 55% were alcoholic and remaining 45% were nonalcoholic. The mean age of presentation in our study was 39.2 years and in alcoholic it was 39.42 years, and nonalcoholic it was 39.07 years. There was a male predominance with males accounting for 90 percent in which 61.1% are alcoholic and 38.9 percent are nonalcoholic with 9:1 male to female ratio. In our study 100 % of patients had tenderness, 3% of alcoholic and 7.4 % of nonalcoholic presented as mass abdomen, and 21.2% alcoholic and 7.4% of nonalcoholic presented as ascites. USG abdomen was diagnostic in 93.3 % of the patients in our study. All of them managed conservatively, of the 8 patients of biliary pancreatitis 7 underwent interval cholecystectomy, and 1 underwent ERCP + ES. Conclusions: Acute pancreatitis is a common cause of acute abdomen. Alcohol being the most common cause of acute pancreatitis in the present study. Nonalcoholic pancreatitis contribute to a significant proportion of etiology of pancreatitis. Prompt identification and diagnostic work up to identify the etiology of pancreatitis followed by appropriate treatment results in cure and prevention of untoward complications.